The effect of BCG on iron metabolism in the early neonatal period: A controlled trial in Gambian neonates. Issue 26 (12th June 2015) - Prentice, Sarah; Jallow, Momodou W.; Prentice, Andrew M.; MRC-International Nutrition Group, b
Abstract Bacillus Calmette-Guerin (BCG) vaccination has been reported to protect neonates from non-tuberculous pathogens, but no biological mechanism to explain such effects is known. We hypothesised that BCG produces broad-spectrum anti-microbial protection via a hepcidin-mediated hypoferraemia, limiting iron availability for pathogens. To test this we conducted a trial in 120 Gambian neonates comparing iron status in the first 5-days of life after allocation to: (1) All routine vaccinations at birth (BCG/Oral Polio Vaccine (OPV)/Hepatitis B Vaccine (HBV)); (2) BCG delayed until after the study period (at day 5); and (3) All routine vaccinations delayed until after the study period. Vaccine regime at birth did not significantly impact on any measured parameter of iron metabolism. However, the ability to detect an effect of BCG on iron metabolism may have been limited by short follow-up time and high activation of the inflammatory-iron axis in the study population.